MODEL PENDANAAN INDUSTRI PERTAHANAN DI INDONESIA - Wibowo, Senopati Yudho; Lestari, Amin; Nugroho, Hervianto (Journal of Industrial Engineering & Management Research, 2022)
. Management of the Industrial Strategy and Defense Industry in the country is almost always faced with three main problems, namely: the development of defense technology that relies on two schemes, Human Resources (HR) Industrial Human Resources (HR). These three problems are sought to be resolved, but Indonesia has a limited budget to strengthen the research and development (R&D) system in the defense sector. Indonesia is targeting to build its own military. However, this requires a large amount of budget. So that the government can make policies related to this. The method used in this paper is a qualitative approach that discusses the Defense Industry Investment model in Indonesia. Data collection is done through literature study. Data from the archival process of data sources through literature study (Library Defense) in the form of books, journals or articles, archives, newspapers, and the internet are then analyzed with relevant theories based on topics. The author discusses several things, namely the role of the budget in supporting the defense industry and the mechanism of sources of financing for the defense industry and the transformation of the defense economy, as well as the dynamics of defense equipment expenditure needs. The results obtained are that until now the Ministry of Defense continues to rely on the "arms maintenance-modernization" model, which according to the proportion of GDP to defense equipment spending is 1-1.5 percent, and has not led to the "modernization-arms build up" model which requires an allocation of 2 percent of defense spending. GDP. The appearance model also shows a design of Rp. 1.7 kualidrun. Indonesia is still difficult to make the technological leaps needed to build a defense force in 2024.